Causes and effects of coastal dunes erosion during storm surge Axel in January 2017 on the southern Baltic Polish coast - Łabuz, Tomasz Arkadiusz (Quaestiones Geographicae, 2023)
The study is dedicated to researching the storm surge Axel, the largest on the South Baltic coast in the 20th and 21st centuries. This unique event resulted in a very large erosion along the whole Polish Baltic Sea coast in January 2017 (max. HSL = 1.65 m, the average for the coast 1.36 m). Storm surge effects on the coast were followed based on field observations of dune retreat and analysis of hydrodynamic and meteorological parameters of the surge and its passage through the Baltic Sea. The material of dune erosion was collected based on cross-shore profiling of almost every 1 km, along the whole Polish sand barrier coast, before and after this storm. The work also studies the parameters of smaller storm surges from the end of 2016, which caused the lowering of beaches and dune erosion. A relationship was observed between erosion, and beach height and sea level (SL). The higher the beach, the lower the erosion that occurred. The average dune toe retreat was 5.1 m, and the largest exceeded 9–19 m (max. 42 m). The most important for dune erosion was the height of run-up, beach height and shore exposition for a surge. The largest dune erosion was observed during the heaviest SL with wave run-up higher than 3.8 m above mean sea level (AMSL). Each coast section was eroded, which also caused losses in infrastructure.